Tools for Ethical Decision Making - Palma-Angeles, Antonette (Archīum Ateneo, 2020)
In this lecture, Dr. Angeles poses an ideal method for decision making when we are faced with an ethical dilemma. Speaker: Antonette Palma-Angeles is Professor at the Ateneo de Manila University where she teaches Ethics and Leadership. She does leadership and business ethics consulting for Philippines companies and is a regular visiting lecturer at Kyoto University’s Asian Business Leadership program. She was formerly Ateneo’s Vice President for the Professional Schools and Academic Vice President. She received her PhD from the Katholieke Universiteit Leuven in Belgium.